Legal medicine aspects of female sterilization: our experience - Fedeli, Piergiorgio; Cecchi, Stefano; Scendoni, Roberto; Cannovo, Nunzia (Frontiers in Medicine, 2023)
Introduction. The most frequent sterilization procedures include postpartum tubal ligation, laparoscopic tubal disruption or salpingectomy, and hysteroscopic tubal occlusion. It may be performed via laparoscopy, mini-laparotomy, or hysteroscopy. Safety, efficacy, short-term complications, long-term complications, and non-contraceptive benefits of sterilization are different for each procedure. Female sterilization has become an important professional liability problem in obstetrics and gynecology.Materials and methods: We analyzed 6 cases of surgical sterilization that have been the subject of civil proceedings. We review indications, contraindications, and complications associated with each sterilization procedure.Results. In our small number of cases, women who have undergone sterilization performed negligently are entitled to recover damages for wrongful conception, negligence, and wrongful birth. We also consider the issue of female sterilization of minors.Discussion. Tubal sterilization can be performed with different techniques, chosen in light of the various situations involved, with the goal of reducing as many as possible any failures. Thorough and complete communication of information is of primary importance.Sterilization is the most widely used birth control method around the world. The procedure is generally safe and highly effective. As reported in the literature, the decision concerning method depends on the setting, the surgeon's experience, the country's economic development, and the woman's preference, but we think that some techniques present a greater risk of failure and expose the surgeon to malpractice litigation.